(untitled) (EAAE Annual Conference Proceedings, 2023)
The Bauhaus was active for only about fifteen years (1919-1933), but despite this short lifespan, it was able to be very influential in the field of education and practice worldwide. This study examines the causes of Bauhaus’s success and global influence from the perspective of the three pillars of each school, teacher, student, and place of education. Bauhaus recruited major, international figures and well-known avant-garde artists associated with prominent artistic groups around the world. Bauhaus also hired aspiring junior masters. This team of teachers made the Bauhaus dynamic, progressive and influential. Students of Bauhaus were young people from over 29 countries. They comprised a relatively diverse group in terms of age, gender, and nationality.